A pharmacovigilance study of pharmacokinetic drug interactions using a translational informatics discovery approach. Issue 4 (23rd February 2021) - Wang, Lei; Shendre, Aditi; Chiang, Chien‐Wei; Cao, Weidan; Ning, Xia; Zhang, Ping; Zhang, Pengyue; Li, Lang
Abstract : Background: While the pharmacokinetic (PK) mechanisms for many drug interactions (DDIs) have been established, pharmacovigilance studies related to these PK DDIs are limited. Using a large surveillance database, a translational informatics approach can systematically screen adverse drug events (ADEs) for many DDIs with known PK mechanisms. Methods: We collected a set of substrates and inhibitors related to the cytochrome P450 (CYP) isoforms, as recommended by the United States Food and Drug Administration (FDA) and Drug Interactions Flockhart table™. The FDA's Adverse Events Reporting System (FAERS) was used to obtain ADE reports from 2004 to 2018. The substrate and inhibitor information were used to form PK DDI pairs for each of the CYP isoforms and Medical Dictionary for Regulatory Activities (MedDRA) preferred terms used for ADEs in FAERS. A shrinkage observed‐to‐expected ratio (Ω) analysis was performed to screen for potential PK DDI and ADE associations. Results: We identified 149 CYP substrates and 62 CYP inhibitors from the FDA and Flockhart tables. Using FAERS data, only those DDI‐ADE associations were considered that met the disproportionality threshold of Ω > 0 for a CYP substrate when paired with at least two inhibitors. In total, 590 ADEs were associated with 2085 PK DDI pairs and 38 individual substrates, with ADEs overlapping across different CYP substrates. More importantly, we were able to find clinical and experimental evidence for the paclitaxel‐clopidogrel interaction associated with peripheral neuropathy in our study. Conclusion: In this study, we utilized a translational informatics approach to discover potentially novel CYP‐related substrate‐inhibitor and ADE associations using FAERS. Future clinical, population‐based and experimental studies are needed to confirm our findings.